Internet preaching as a new format of religious communication - Miletova, Ekaterina V. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2024)
The article is devoted to the analysis of English-language Internet sermons presented in video format in the digital environment. According to the author, a video sermon is an innovative form of religious communication; its prevalence is determined both by the information technology development and by the possibility of prompt and large-scale broadcast and popularization of religious teaching ideas. The research material is sermons posted on the Internet (the total sample size is 500 video sermons). The article emphasizes the ambiguous nature of online preaching, highlighting its positive and negative aspects. The advantages of online preaching include a wide range of target audiences, focus on educating young people and interacting with disabled people. In turn, among the negative manifestations of online preaching are lack of motivation among the addressee, the emergence of conflict situations in matters of religion and the emergence of its radical forms, movements, sects, changes in the social status of the clergyman (preacher). As differential features of online sermons, we identify: 1) non-canonical nature and lack of church recognition; 2) the dependence of the success of the sermon on both the personal and acting characteristics of the preacher, his charisma; 3) a change in the image of the clergyman and his identification with a mere mortal in the minds of believers. Particular attention is paid to describing the linguistic features of online sermons. According to the analysis of the practical material, online sermons in video format are characterized by the use of generalizing appeals, emotional and evaluative vocabulary, metaphors, and modal verbs. As for the content and structure of video sermons, the author notes the presence of allusions to precedent religious texts, stories, anecdotes, etc., entertaining the addressee.